Museums & galleries displaying Korea's past and future - Jackson, Ben; Park, Hye-young; Seungeun, Euna Yoo; Eun-ji, Shin (Seoul Korea Foundation Seoul Selection, 2011)
Overview of selected major national and public museums in Seoul, South Korea, as well as the specialized museums and regional national museums.
"The content of this series is based on the material published in Koreana, the Korea Foundation's full-color quarterly featuring in-depth coverage of various aspects of Korea's cultural themes"--cover flap
Keywords: Museums -- Korea (South) -- Guidebooks; Art museums -- Korea (South) -- Guidebooks